Peran Usaha Mikro, Kecil, dan Menengah (UMKM) dalam Kesejahteraan Perekonomian Negara dan Masyarakat - Satriaji Vinatra (Lembaga Pengembangan Kinerja Dosen, 2023)
In economic activities, welfare is the main thing for the community. This welfare can be seen by the ability of the community to fulfill their daily needs. Micro, Small and Medium Enterprises are productive businesses that are owned and managed by individuals or business entities that have met the criteria as micro-enterprises. With the existence of MSMEs, fulfilling these needs becomes more easily accessible to people throughout Indonesia. This study aims to analyze the role of Micro, Small and Medium Enterprises (MSMEs) in the economy. MSMEs have an important role in creating economic growth, employment, and reducing social inequality. In this journal, we present a comprehensive literature review on the contribution of MSMEs to the economy and the factors that influence the success of MSMEs. We also discuss policy initiatives that support the development of MSMEs and provide recommendations for increasing the role of MSMEs in the economy. Keywords: The Role of MSMEs, State Economic Welfare, Community Welfare